Effects of elevated CO2 on the extractable amino acids of leaf litter and fine roots. Issue 4 (18th March 2014) - Top, Sara M.; Filley, Timothy R.
Summary: Elevated atmospheric CO2 concentrations can change chemistry and input rate of plant tissue to soil, potentially influencing above‐ and below‐ground biogeochemical cycles. Given the important role played by leaf and root litter chemistry in controlling ecosystem function and vulnerability to environmental stresses, we investigated the hydrolyzable amino acid distribution and concentration in leaf and fine root litter among control and elevated CO2 treatments at the Rhinelander free air CO2 enrichment (FACE) experiment (WI, USA). We extracted hydrolyzable amino acids from leaf litter and fine (< 2 mm) roots at three depths for both control and elevated CO2 plots. We found that elevated CO2 decreased the proportion of total leaf amino acid carbon (C), but had no effect on total leaf amino acid nitrogen (N). There was no treatment effect for total root amino acid N or amino acid C for any depth. The decrease in leaf amino acids is probably a result of the shift of protein compounds to more structural compounds. Despite the decrease in leaf amino acid C concentrations, the overall increase in annual plant production under elevated CO2 would result in an increase in plant amino acids to the soil.